Risk Mitigation Strategies in the Implementation of Digital Banking Technology: A Case Study of Bank X In Indonesia - Siswanto, Fatchullah Reza; Kholmi, Masiyah (Politeknik Negeri Jember, 2025)
This study aims to determine the risk mitigation practices in implementing digital technology at Bank X. This research is a qualitative case study of Bank X, which received the best digital services award. The primary data used in this study were obtained from interviews and observations, while the secondary data were obtained from company documentation on risk mitigation efforts. The stages of data analysis were data reduction, presentation, and conclusion-drawing. The findings reveal that both internal and external users of Bank X utilize different digital technologies to access banking services. For internal users, digital banking is employed for nearly all operational banking activities, whereas external users leverage it to facilitate transactions for both individual and institutional customers. Bank X implements intensive risk-mitigation measures to prevent cybercrimes associated with technology use. This study was conducted at Bank X, which only captures the implementation of digital technology at Bank X. Future studies could conduct multi-case testing to obtain more general results across Islamic banks.